Analysis of Islamic Tourism Potential Development in Kerinci - Mashuri; Iskandar; Yamin, Martinis (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2024)
This research analyzes the 3A concept and concludes the SWOT concept in developing Islamic Tourism Potential in Kerinci. The research method used is a qualitative-descriptive approach, using field observation, interviews and literature study methods. The analysis was carried out using the Miles and Herberman interactive analysis model and SWOT analysis. Research found that Islamic Tourism in Kerinci has become a tourist icon for this region, with a number of other supporting tourist attractions that have great potential. However, there are still several obstacles that hinder the development of this tourist area. Therefore, alternative tourism development strategies can help encourage the development of this area to become more advanced and meet the required needs